Two new species of genus Hydrosmittia Ferrington & Sæther (Diptera: Chironomidae) from China - Zhang, Ruilei; Liu, Wenbin; Ferrington, Leonard C. Jr; Wang, Xinhua (Zootaxa, 2016)
The genus Hydrosmittia from China is reviewed. Two new species H. continalinea sp. n. and H. sipinata sp. n. are described and illustrated based on male imagines. Key to known male imagines of genus Hydrosmittia worldwide is provided.